Organic Cation Transporter 1 (OCT1) mRNA expression in hepatocellular carcinoma as a biomarker for sorafenib treatment. Issue 1 (December 2016) - Grimm, Daniel; Lieb, Jonas; Weyer, Veronika; Vollmar, Johanna; Darstein, Felix; Lautem, Anja; Hoppe-Lotichius, Maria; Koch, Sandra; Schad, Arno; Schattenberg, Jörn; Wörns, Marcus; Weinmann, Arndt; et al.
Abstract Background The polyspecific organ cation transporter 1 (OCT1) is one of the most important active influx pumps for drugs like the kinase inhibitor sorafenib. The aim of this retrospective study was the definition of the role of intratumoral OCT1 mRNA expression in hepatocellular carcinoma (HCC) as a biomarker in systemic treatment with sorafenib. Methods OCT1 mRNA expression levels were determined in biopsies from 60 primary human HCC by real time PCR. The data was retrospectively correlated with clinical parameters. Results Intratumoral OCT1 mRNA expression is a significant positive prognostic factor for patients treated with sorafenib according to Cox regression analysis (HR 0.653, 95 %-CI 0.430-0.992;p = 0.046). Under treatment with sorafenib, a survival benefit could be shown using the lower quartile of intratumoral OCT1 expression as a cut-off. Macrovascular invasion (MVI) was slightly more frequent in patients with low OCT1 mRNA expression (p = 0.037). Treatment-induced AFP response was not associated with intratumoral OCT1 mRNA expression levels (p = 0.633). Conclusions This study indicates a promising role for intratumoral OCT1 mRNA expression as a prognostic biomarker in therapeutic algorithms in HCC. Further prospective studies are warranted on this topic.